2020
DOI: 10.1073/pnas.2013921117
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 drives HPV+ HNSCC sensitivity to WEE1 inhibition

Abstract: Head and neck squamous cell carcinoma (HNSCC) associated with high-risk human papilloma virus (HPV) infection is a growing clinical problem. The WEE1 kinase inhibitor AZD1775 (WEE1i) overrides cell cycle checkpoints and is being studied in HNSCC regimens. We show that the HPV16 E6/E7 oncoproteins sensitize HNSCC cells to single-agent WEE1i treatment through activation of a FOXM1-CDK1 circuit that drives mitotic gene expression and DNA damage. An isogenic cell system indicated that E6 largely accounts for these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 59 publications
6
17
0
Order By: Relevance
“…Thus, one model would predict that cells with reduced FOXM1 would have a reduced rate of inherited DNA damage caused by RHNO1 loss ( Cotta-Ramusino et al, 2011 ) due to reduced cell cycle transit of cells with damaged DNA. This model seems to be in agreement with recent reports showing that FOXM1 sensitizes tumor cells to Chk1 and WEE1 inhibitors ( Chung et al, 2019 ; Branigan et al, 2021 ; Diab et al, 2020 ). In contrast, because FOXM1 is also required for proper mitotic progression and disruption of FOXM1 increases mitotic DNA damage ( Laoukili et al, 2005 ), it is plausible that targeting FOXM1 could, in some instances, augment the effects of RHNO1 depletion.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, one model would predict that cells with reduced FOXM1 would have a reduced rate of inherited DNA damage caused by RHNO1 loss ( Cotta-Ramusino et al, 2011 ) due to reduced cell cycle transit of cells with damaged DNA. This model seems to be in agreement with recent reports showing that FOXM1 sensitizes tumor cells to Chk1 and WEE1 inhibitors ( Chung et al, 2019 ; Branigan et al, 2021 ; Diab et al, 2020 ). In contrast, because FOXM1 is also required for proper mitotic progression and disruption of FOXM1 increases mitotic DNA damage ( Laoukili et al, 2005 ), it is plausible that targeting FOXM1 could, in some instances, augment the effects of RHNO1 depletion.…”
Section: Discussionsupporting
confidence: 93%
“…FOXM1 may also act as a therapeutic target against head and neck carcinoma [59,60]. Recent study showed that upregulated basal FOXM1 activity predisposes HPV positive HNSCC to WEE1i-induced toxicity [61]. Consistently, we found that FOXM1 is differentially expressed in OSCC patient with different tumor stages, genders, races, and molecular subtypes.…”
Section: Discussionsupporting
confidence: 83%
“…With respect to additional genetic alterations that could benefit from PKMYT1 inhibition, tumors with mutations in FBXW7, which encodes a substrate adaptor for a cullin-RINGligase that targets cyclin E for ubiquitin-dependent proteolysis (11,(47)(48)(49), represents an attractive patient population given that cyclin E drives genome instability in these tumors (50). We finally note that alterations in FOXM1-MMB-driven transcription are seen in multiple cancers (51-53), including HPV-positive head and neck squamous cell carcinoma, where it causes sensitivity to WEE1 inhibition (54). Therefore, testing whether FOXM1-MMB-driven transcription can act as a more general vulnerability to the loss of CDK1 inhibitory phosphorylation may further expand the range of tumors that could benefit from PKMYT1 inhibitors.…”
Section: Discussionmentioning
confidence: 98%